On wafer probing of monolithic microwave integrated circuit capacitors / Nor Asmah Ahmad - Ahmad, Nor Asmah (2007)
The purpose of this project is to measure capacitor on silicon wafer using Cascade's probe. The wafer will be measured using the RF probing technique. This project also will design the interdigital capacitor which focuses on the simulation with different length and width. The silicon has been used as a substrate with Er = 11.7 and thickness=300μm. The circuits were simulated using CAD packages.